The Political Economy of Propaganda: Evidence from US Newspapers - Sebastian Ottinger; Max Winkler (Institute of Labor Economics (IZA), 2022)
We study the impact of the first American party committed to redistribution from rich to poor on anti-Black media content in the 1890s. The Populist Party sought support among poor farmers, regardless of race, providing the segregationist Democratic establishment in the South with an incentive to fan racial outrage to alienate white voters from the Populists. Using text data from local newspapers and a difference-in-differences strategy, we find that stories of sexual assaults by Black men on white women became more prevalent in counties where the Populists threatened the Democratic dominance, and in Democratic newspapers only.
Keywords: D72; J15; L82; N91; Z1; 330; propaganda; divide and rule; political threat; media